Implementation Aspects of Wigner-Hough Transform Based Detectors for LFMCW Signals - Guner, Kani K.; Erkmen, Burcu; Gulum, Taylan O.; Erdogan, A. Yasin; Yildirim, Tulay; Ata, Lutfiye Durak (IEEE, 2016)
Linear Frequency Modulated Continuous Waveform (LFMCW) waveforms are widely used in Low Probability of Intercept (LPI) radars. In this work, Wigner-Hough based transforms are used to detect such waveforms. They are investigated for three aims: Minimizing the effects of Wigner-Ville Distribution (WVD) cross-terms in the transforms, reducing the complexity of hardware implementation and producing the transform results faster. Modified Wigner- Hough Transform (MWHT) is analyzed for the first aim. Sample and hold type intermediate sampling and column-based thresholding techniques are examined for the second and third aims. A signal database (3000 signals with different SNR levels) is created and used to evaluate the performances of 8 alternative methods on probability of detection and probability of chirp rate estimation. The results are compared for -3dB down to -14dB SNR levels. Proposed method is found to be the best candidate to be implemented on Field Programmable Gate Arrays (FPGA) since it produces better performance with less computational density.
Keywords: Column-based Thresholding; FPGA; LFMCW; LPI radar; Modified Wigner-Hough Transform; DISCRETE-TIME; Computer Science; Imaging Science & Photographic Technology; Telecommunications